Manajemen Pengembangan Kurikulum Jurusan Pendidikan Agama Islam (PAI) di Sekolah Tinggi Ilmu Tarbiyah Palapa Nusantara Lombok Timur - Nasrullah, Nasrullah (YASIN, 2022)
Study this aim for know and analyze management development curriculum Major PAI in College of Science Tarbiyah Palapa Nusantara (STITPN) East Lombok, namely ; Study this use approach qualitative with method studies case . As for the procedure data collection is done with observation , interview and study documentation . And for data analysis performed with using an interactive model . .Results study show that ; First , planning curriculum arranged with use approach consolidation and solution problem with take into account internal and external factors , future developments as well as factor not always sure _ attached to every change . Second , organizing curriculum arranged based on decision Minister of National Education No. 232 of 2000 which consists of from : Subject Development Personality (MPK), subjects expertise and knowledge (MKK), subjects Skill Works (MKB), Subjects Behavior Works (MPB), and Subjects alive Community (MBB). Third , implementation is factor most important from development curriculum , for that arranged a number of stages and steps strategic for success implementation in the field , including : (1) program socialization ; (2) compose teaching team ,; (3) develop atmosphere academic ; (4) development of learning strategies and models ; (5) development study quality ; (6) monitoring system , evaluation curriculum conducted by continuous and comprehensive start from content , input , process, and product (CIPP) . as for stages evaluation covers formative , summative and workshop